Numerical simulation of the dynamic evolution of effective stress and pore water pressure within a rock matrix - Hu, Jiangchun; Zhou, Wenqing; Ren, Zhihao; Liu, Miao; Liu, Bing (Frontiers in Earth Science, 2025)
The dynamic evolution of effective stress and pore water pressure is a key scientific issue of study in the field of seepage-stress coupling in geotechnical engineering. To address the imbalance in effective stress redistribution caused by pore water pressure anomalies during water surges in underground engineering, the study employed numerical simulations to reveal the dynamic evolution of effective stress and pore water pressure within the sandstone matrix. The simulation was conducted by developing a coupled granular flow-permeability model in PFC6.0, which accounts for pore water pressure transfer. The model was calibrated through parameter inversion based on UCS experimental results, and a triaxial consolidation-relaxation test was designed using the model and calibrated parameters. The parameter calibration results indicate that the four key mesoscale parameters—tensile strength, cohesion, internal friction angle, and modulus of elasticity—obtained through inverse calibration, allow the numerical test results to deviate from the actual experimental results by only 1.3%. The numerical simulation results reveal the following findings: 1) The effective stress response of rocks under constant confining pressure conditions consistently shows peak strength characteristics. 2) A strong positive correlation exists between the confining pressure stress level and the peak effective stress. 3) The evolution of effective stress before the rock reaches peak stress follows a nonlinear pattern, initially decreasing and increasing, with the final value asymptotically approaching the level of peripheral confining pressure. The study’s findings on the dynamic evolution of effective stress and pore water pressure provide a crucial theoretical foundation for predicting water influx in deep tunnels and optimizing fracturing processes in shale gas reservoirs.